Ustekinumab for the treatment of recalcitrant pyoderma gangrenosum: A case report - Vallerand, Isabelle A (SAGE Open Med Case Rep, 2019)
Pyoderma gangrenosum is an ulcerating disease associated with a high degree of morbidity and mortality. Currently, little is known about the pathophysiology of pyoderma gangrenosum, though it has been linked to increased levels of inflammatory cytokines including interleukin-23. As pyoderma gangrenosum is a rare disease, evidence for pyoderma gangrenosum treatment is dependent on reporting of cases with successful therapies. Here, we describe a case of pyoderma gangrenosum developing on the lateral leg of a medically complex 47-year-old male already on chronic immunosuppressive therapy, who achieved successful wound healing with the use of ustekinumab, a monoclonal antibody targeting inhibition of interleukin-12 and interleukin-23. This case lends further evidence for the role of interleukin-23 in the pathogenesis of recalcitrant pyoderma gangrenosum and also suggests that healthcare providers may consider a trial of ustekinumab in pyoderma gangrenosum that has failed previous topical treatments or systemic immunosuppression.